THE USE OF DIGITAL TECHNOLOGIES IN EDUCATION: STRATEGIES FOR ENHANCING EFFECTIVENESS - Anvar Khurramov (Proximus Journal Publishing, 2025)
The integration of digital technologies in education has transformed traditional teaching and learning processes, offering new opportunities for enhancing effectiveness and engagement. This study explores innovative strategies for utilizing digital tools to improve educational outcomes. It focuses on leveraging interactive platforms, adaptive learning systems, and AI-driven applications to personalize learning experiences. The research also examines challenges such as digital literacy gaps and infrastructure limitations, proposing solutions to maximize the potential of digital technologies. Emphasis is placed on teacher training, effective implementation methods, and fostering a digital culture in educational institutions. The findings aim to provide actionable insights for educators, policymakers, and stakeholders
Keywords: policymakers; stakeholders; educational institutions